2012
DOI: 10.1542/peds.2011-3148
|View full text |Cite
|
Sign up to set email alerts
|

Lower Life Satisfaction Related to Materialism in Children Frequently Exposed to Advertising

Abstract: Among 8- to 11-year-old children, life satisfaction leads to decreased materialism and not the other way around. However, this effect only holds for children who are frequently exposed to television advertising. It is plausible that the material values portrayed in advertising teach children that material possessions are a way to cope with decreased life satisfaction. It is important to reduce this effect, because findings among adults suggest that materialistic children may become less happy later in life. Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 28 publications
4
50
0
6
Order By: Relevance
“…When it comes to life satisfaction, there may be a third explanation for not finding a correlation to the MVS-c. Research has shown that low life satisfaction can lead to higher levels of materialism but that being more materialistic does not decrease life satisfaction in children (Opree et al 2012). It is thought that children who are dissatisfied with their lives may seek happiness and fulfillment in material possessions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When it comes to life satisfaction, there may be a third explanation for not finding a correlation to the MVS-c. Research has shown that low life satisfaction can lead to higher levels of materialism but that being more materialistic does not decrease life satisfaction in children (Opree et al 2012). It is thought that children who are dissatisfied with their lives may seek happiness and fulfillment in material possessions.…”
Section: Discussionmentioning
confidence: 99%
“…Goldberg et al (2003) found that materialistic children, more often than less materialistic children, asked their parents to buy a product that they had seen on TV. Lastly, life satisfaction was negatively related to materialism (Kasser 2005;Opree et al 2012): Children who were less satisfied with their life tended to be more materialistic than other children.…”
Section: Validating the Mvs-cmentioning
confidence: 99%
“…Furthermore, Chan's (2007) work with Hong Kong Chinese youths found that materialistic teenagers tend to watch more television, and engage in more social comparison with their friends as well as with celebrities. Opree et al's (2012) longitudinal study with Dutch children showed that materialistic children who are exposed to extensive television advertisements tend to subsequently report lower well-being. These findings, coupled with SDT's argument about intrinsic and extrinsic goals and their influences on well-being and life satisfaction, suggest it is very likely that the negative link between materialism and life satisfaction among adults may exist among adolescents as well.…”
Section: Materialism and Life Satisfactionmentioning
confidence: 99%
“…No presente estudo, não se utilizou uma escala para examinar o nível de desenvolvimento moral dos participantes, o que, talvez, possa contribuir para o entendimento dos resultados conflitantes encontrados na literatura em relação à influência etária. Conforme mencionado, estudos têm associado a exposição à mídia (televisão e internet) com os níveis de materialismo (Opree, Moniek, & Valkenburg, 2012;Sirgy et al, 2012). Os dados coletados confirmaram parcialmente os achados desses estudos, uma vez que a exposição à internet apresentou correlação significativa com os níveis de materialismo enquanto que a exposição à televisão não confirmou esta tendência.…”
Section: Discussionunclassified
“…Pesquisas têm enfatizado a relação entre a exposição à mídia (televisão e internet) com os níveis de materialismo. De acordo com a literatura, estas variáveis estão relacionadas aos níveis de consumo: quanto maior a exposição à televisão e à internet, maiores os níveis de materialismo em adolescentes (Opree, Moniek, & Valkenburg, 2012;Sirgy et al, 2012). Chia (2010), refere que a relação da exposição à televisão com o aumento do materialismo acontece em função das propagandas veiculadas, as quais mostram aos adolescentes que eles podem realizar suas metas de vida por meio da aquisição de bens materiais, utilizando uma forma de persuasão para que eles considerem as posses materiais como as próprias metas de vida.…”
Section: Materialismounclassified